Assessing over Time: The Political Science Program Review. - Deardorff, Michelle D. (PS: Political Science & Politics, 2016)
The article offers information on the a symposium on reviewing the political science program. Topics discussed include educational evaluation has moved beyond regional accreditors as universities and colleges have institutionalize the culture of assessment through academic program review, and implementation of strategies by carious departments to enhance the potential impact of the process.